ANALISIS MAKNA PADA PEPACCUR ADEK ANJAK LEBEU DALAM BUKU SASTRA LISAN LAMPUNG DIALEK PUBIAN - Fauzi , Irfan; Budiman , Ahmad Arif; Prayogi , Rahmat; Riadi , Bambang (FKIP Universitas Lampung, 2024)
This research describes the analysis of the meaning of Pepaccur Adek Anjak Lebeu in the book Lampung Oral Literature Pubian Dialect. The problem formulation was found about